PEMENUHAN HAK EKONOMI SOSIAL BUDAYA MASYARAKAT NELAYAN PASIR JAMBAK DI KELURAHAN PASIA NAN TIGO KOTA PADANG - Ratna Sari; Deded Chandra (JURNAL BUANA, 2022)
This study aims to descibe how to fulfil the socio-cultural economic rights of the fishing community of Pasir Jambak in Pasia Nan Tigo Village, Padang City. This type research is a qualitative. Informants this study were determined by purposive sampling. Data collection techniques used in the form of observation, interviews and documentation. Research results say (a) The fulfillment of socio-cultural economic rights of the fishing community is related to the fulfillment of education in terms of the availability of existing formal institutions, namely the high scholl level, while the school facilities are adequate. (b) The fulfillment of the socio-cultural economic rights of the fishing community related to the fulfillment of proper housing in terms of housing conditions for the fishing community is still not feasible from the physical condition, the housing for the fishing community has not been fulfilled on the feasibility of a healthy house. This means that there are still fishing community houses that do not have toilets, still us MCK, and fishing community housing is not safe. This means that there are still people’s houses near the beach, and flooding when it rains heavily.